Adverse events of immune checkpoint therapy alone versus when combined with vascular endothelial growth factor inhibitors: a pooled meta-analysis of 1735 patients - Kovalenko, Iuliia; Lynn Ng, Wern; Geng, Yimin; Wang, Yinghong; Msaouel, Pavlos; Bhatia, Shailender; Grivas, Petros; Benkhadra, Raed; Alhalabi, Omar (Frontiers in Oncology, 2024)
Background Combining immune checkpoint therapy (ICT) and vascular endothelial growth factor inhibitors (VEGFi) may result in increased treatment-related and immune-related adverse events (TRAEs and irAEs) compared to ICT alone. This metanalysis was conducted to identify prospective phase II or III clinical studies that evaluated the toxicity profile of ICT + VEGFi compared to ICT alone. Methods: A systematic search was performed across all cancer types and major databases until August 10, 2022, and screening was done by two independent investigators. Inclusion criteria included phase 2 or 3 studies with at least one arm of patients treated with combination therapy and one arm treated with monotherapy. Adverse event data were pooled using a restricted maximum likelihood fixed effects model, and heterogeneity using Cochran’s Q (chi-square) test. Results: 7 out of 9366 studies met the inclusion criteria, and 808 and 927 patients were treated with ICT monotherapy and a combination of ICT with VEGFi, respectively. Only one study reported irAEs, so the analysis was restricted to TRAEs. The total number of TRAEs was significantly higher in the ICT + VEGFi group (RR:1.49; 95% CI 1.37 -1.62; p=1.5×10-21), and more frequent treatment withdrawals were attributed to TRAEs (RR:3.10; 95% CI 1.12-8.59; p=0.029). The highest TRAE effect size increases noted for rash (RR 6.50; 95% CI 3.76 – 11.25; p=2.1×10-11), hypertension (RR:6.07; 95% CI 3.69–10.00; p=1.3×10-12), hypothyroidism (RR:5.02; 95% CI 3.08 – 8.19; p=8.9×10-11), and diarrhea (RR:4.94; 95% CI 3.21–7.62; p=3.8×10-13). Other significantly more frequent TRAEs included nausea, anemia, anorexia, and proteinuria. Conclusion: Combination therapy with ICT and VEGFi carries a higher risk of certain TRAEs, such as rash, hypertension, hypothyroidism, diarrhea, nausea, anorexia, and proteinuria, compared to ICT monotherapy. More granular details on the cause of AEs, particularly irAEs, should be provided in future trials of such regimens.